Analisis Pengaruh Pembangunan Infrastruktur dan Investasi Terhadap PDRB di Provinsi Sumatera Selatan - Galuh Andani Sunuputri; Maulidiyah Indira Hasmarini (Ekonomis: Journal of Economics and Business, 2023)
Infrastructure is the main key in economic activity in an area, the availability of qualified infrastructure will make it easier for the community to carry out economic activities, so that the economy runs efficiently, people's incomes increase, and the expected economic growth can be achieved. This study aims to estimate the direction and magnitude of the influence of infrastructure development in the sectors of education, health, roads, household electricity supply, and domestic investment on Gross Regional Domestic Product (GRDP) in 17 Regencies or Cities in South Sumatra Province during 2016- 2021 by using panel data regression. The results of the selected model, namely Fixed Effects, show that infrastructure development in the education, health, electricity supply, and domestic investment sectors has a positive effect on GRDP. Meanwhile, road construction was found to have no effect on GRDP in South Sumatra Province. Based on these results, the government in each region and the government of South Sumatra Province can synergize in increasing development on variables that are proven to have a significant effect on regional income and GRDP. The construction of new schools and health facilities at the lowest level such as villages needs to be improved so that residents can access these two things more easily, so that the quality of human beings in South Sumatra can improve and the economy and GRDP in each region will also increase.